A Case Study on Building Information (BIM) and Land Information (LIM) Models Including Geospatial Data - Borkowski, Andrzej Szymon; Kochański, Łukasz; Wyszomirski, Michał (Geomatics and Environmental Engineering, 2022)
Landscape information modeling (LIM) is a new trend in spatial projects made using BIM technology. Elements of land development are, not only in the opinion of the authors, just as essential as the element of a building object. In turn, GIS data can be used to model larger areas based on combined data from GIS and BIM models. The lack of the strict integration of BIM and GIS (ISO/TR 23262:2021 covers GIS/BIM interoperability, ISO 19166 is in preparation) prevents the modeling of land development objects, both existing and planned, in many cases. The modeling process using the current and known BIM tools and processes were presented to efficiently develop a model of a building object with its surroundings. Modeling took place using best practices that are collected and used in the Polish reality. The work presents an object-oriented approach to modeling elements of spatial development with the preservation of the so-called occupational hygiene. By applying the above principles, it is possible to develop a “good” LIM model that fits the current trends and developments in BIM.